Improvement of Air Gap Membrane Distillation (AGMD) by Peltier’s Effect and Condensation Plate Modifications - Bin Bandar, Khaled (KAUST Research Repository, 2019)
Water is undoubtedly a key life element. Its importance is very clear from a religious perspective:

“We made from water every living thing. Will they not then believe?”
Surah Al-Anbiya verse 30

Also as highlighted in the United Nations resolution 64/292 which recognizes water as a basic necessity for human survival. As the world water demand grows, so does the need to use renewable water sources most available in the form of saline ocean water. Desalination of this water for potable use relies mainly on thermal and membrane-based technologies, mainly multi-stage flash (MSF), multi-effect distillation (MED), and seawater reverse osmosis (SWRO). However, these mature technologies are recognized for their high energy and chemicals use. To cope with these challenges, development of novel desalination processes is required to assure more sustainable water supply for the future. Membrane distillation (MD) has emerged as a process which combines advantages of both membrane and thermal technologies. It has a potential of being cost effective by utilizing renewable or waste heat energies as a driving force. Air gap membrane distillation (AGMD) is one of the four main MD configurations. AGMD’s main feature is the presence of an air gap which is enclosed between the membrane behind which flows the hot feed and condensation surface behind which flows a coolant. While improving the heat transfer across the membrane, the air gap negatively affects mass transfer resistance thereby reducing vapor flux and increasing process footprint.

This dissertation investigates the effect of condensation plate surface modifications on AGMD process efficiency. The modifications are made by utilizing three different approaches including alterations of the surface shape and surface coating (to modify its contact angle) and by varying module inclination angle. A numerical simulation is carried out to determine the key factors which facilitate AGMD vapor flux increase. The second part of this thesis focuses on developing a promising novel approach utilizing Peltier’s process as a heat source to operate the MD process with less energy requirement.

The morphological modifications of a plate surface positively affected vapor flux because of the air gap reduction. The highest vapor fluxes were observed when condensation plate had hydrophilic coatings. Based on the observed results, a thin film-wise condensation was suggested as a primary condensation mechanism. The formed film reduced the air gap thickness and this effect was more prominent at 45° when condensation plate was positioned over the membrane surface. A 2-dimensional mathematical model was developed and the model results agreed with the experimental data. Finally, the thermocouple-based MD concept was introduced and experimentally validated.